Analisis Sosiologi Pengetahuan Terhadap Kitab Ahkam Al-Qur’an Karya Ibn Al-‘Arabi - Faizah, Fatikhatul (Program Studi Ilmu Al-Qur`an dan Tafsir, Fakultas Ushuluddin, UIN Sunan Kudus, 2020)
This article discussed about the interpretation of Ahkam al-Qur’an study of the interpretation of AbuBakr Muhammad bin ‘Abdullah al-Ma'ruf bin al-’Arabi. The main problems that will be answered are; first, what are the external realities that influence the thought of Ibn al-’Arabi in the interpretation of Ahkam al-Qur'an. Second, what is the process of objectivation that is built up in the commentary Ahkam al-Qur’an. Third, how can existing objective reality be formulated by Ibn al-Arabi in the form of internalization through Ahkam al-Qur’an so as to produce a product of contextual interpretation in the era.This study used the analysis of sociology of Peter L. Berger's knowledge. Some of the stages that were passed were in the form of inventorying data, selecting and classifying it, then reconstructing and conducting a critical analysis of the basic assumptions.The results of this study included; First, in terms of externalization, the sociology of knowledge aims to see the outpouring of the ideas of Ibn al-abiArabi in the book Ahkam al-Qur’an, where the ideas were born from the socio-political context of Andalusia. Second, the process of objectification of Ibn al-’Arabi is an objective reality which he developed through his scientific and thought methodology. Simply put, the science and mindset shown by Ibn al-Arabi is reflected in his views on the Koran and interpretation, commentary bi al-ma’sur, and the verses of law. Third, as a result of the objective reality gave birth to the internalization process. This process is purely an individual product, but at the same time as a social product, because no alternative thought arises except departing from thinking that is generally considered to have been established. In the context of the discourse developed by Ibn al-’Arabi, the alternation processes are present in between the substance of Ibn al-Arabi's thought which shows its objective reality. Thus, the internalization process is always present as a result of direct consequences of existing objective reality.This can be deduced from the characteristics of Ibn al-‘Arabi's thought inherent in the commentary Ahkam al-Qur’an. However, as far as this research is concerned, there is something unique and distinctive that is presented by Ibn al-Arabi, namely its moderation in responding to various differences of understanding in interpretation. Besides his bigotry also does not make him blasphemers for those who differ in understanding, he remains a student who always respects the teachers he has quoted in his commentary.